Epidemiology of General, Central Obesity and Associated Cardio-Metabolic Risks Among University Employees, Ethiopia: A Cross-Sectional Study - Janakiraman B (Dove Medical Press, 2020)
Balamurugan Janakiraman,1 Solomon Mekonnen Abebe,2 Mulugeta Bayisa Chala,1,3 Solomon Fasika Demissie1 1Department of Physiotherapy, College of Medicine and Health Sciences, School of Medicine, Gondar University Specialized Comprehensive Hospital, University of Gondar, Gondar, Ethiopia; 2Department of Human Nutrition, Institute of Public Health, College of Medicine and Health Science, University of Gondar, Gondar, Ethiopia; 3School of Rehabilitation Therapy, Queen’s University, Kingston, ON, CanadaCorrespondence: Balamurugan JanakiramanDepartment of Physiotherapy, College of Medicine and Health Sciences, School of Medicine, Gondar University Specialized Comprehensive Hospital, University of Gondar, Gondar, EthiopiaEmail bala77physio@gmail.comBackground: Evidence suggests that middle and low-income countries such as Ethiopia are facing the growing epidemic of both communicable and non-communicable diseases creating a burden on their economy and healthcare system. The increasing prevalence of non-communicable diseases is attributed to sedentarism, lifestyle changes, nutritional transition, and the presence of other cardiometabolic risk factors. Therefore this study was designed to assess the prevalence and association of overweight, obesity, and cardio-metabolic risks and to explore if there was any agreement among the anthropometric measurements among the academic employees of the University of Gondar, Ethiopia.Methods: An institutional-based cross-sectional study was conducted using the WHO stepwise approach and recommendations on 381 academic staff of the university. In addition, physical measurements such as weight, height, waist and hip circumferences, and biochemical measures such as blood pressure and fasting blood glucose level (peripheral blood samples by finger puncture) were measured using standardized tools.Results: The mean age of the participants was 33.5 (95% CI: 32.7, 34.2) years. The prevalence of obesity among the study participants calculated by body mass index, waist circumference (WC), waist-height ratio (WHtR), and waist-hip ratio (WHR) was 13.1%, 33.6%, 51.9%, and 58.5% respectively. The prevalence of diabetes was 4.7% among which 1.3% was not diagnosed prior to this study. About 53 (13.9%) of the study sample were found to be hypertensive (HTN) (6.3% known versus 29 7.6% newly diagnosed). Among the participants, 39.4% and 23.4% were found to be pre-hypertensive and pre-diabetic respectively. WC was significantly associated with hypertension (AOR = 5.14; 2.503, 9.72), pre-DM (AOR = 4.03; 2.974, 5.96), DM (AOR = 3.29; 1.099, 6.01). In addition, WHtR was significantly associated with Pre-HTN (AOR = 2.69; 1.49, 4.58), HTN (AOR = 2.066; 1.008, 6.31), and DM (AOR = 1.855; 0.76, 4.32). On the contrary, both WHR and general obesity measured by BMI were not significantly associated with pre-HTN, HTN, pre-DM and DM groups.Conclusion: This study results revealed the variable prevalence between general obesity and the anthropometric indices (IDF cutoff) defining central obesity; WC, WHtR, and WHR among the participants. The result of this study suggests that the constructs of central obesity, not BMI has to be used to screen risks of cardio-metabolic risks among Ethiopians.Keywords: central obesity, diabetes mellitus, hypertension, prehypertension, prediabetes, Ethiopia